DAYA SANGGA TANAH TERHADAP KADMIUM SERTA PENGARUH PENAMBAHAN SISA TANAMAN TERHADAP PERTUMBUHAN DAN PRODUKSI PADI VARIETAS IR-64 - Katharina Oginawati (Purifikasi, 2010)
A study on soil buffering capacity to cadmium and addition of paddy hay, and the effects on paddy (IR-64 variety) growth and production has conducted in a green house of Environmental Engineering Laboratory of ITB and Bogor Research Center and Development for Food Crop. Latosol soil from Ciparay, South Bandung Regency was used in this research. The aim of the research was to investigate the buffering capacity of the soil to cadmium and the effects of paddy hay addition of 10 tonnes/acre on rice growth and productivity. Statistical method used is group random design with eight treatment combinations and three repetitions. Advanced test was then employed by using Duncan’s Multiple Range Test (DMRT) in 5% level. Treatments given were different concentration levels of cadmium in the water which would be applied to the plants. These concentrations were A0 (0 mg/L), A1 (0,12 mg/L), A2 (0,50 mg/L), and A3 (10 mg/L). Whereas treatment of paddy hay addition were: control (B0) and 40 g in every treated pot (B1). The results showed that latosol soil had a good buffering capacity to cadmium (99,77% without paddy hay addition) and better result with paddy hay addition (99,86%) at 10 mg/L cadmium treatment. Addition of paddy hay with cadmium concentration treatments did not significantly affect the production of IR-64 variety paddy.